Studies Presented to George M. A. Hanfmann - Pedley, John Griffiths; Mitten, David Gordon (1971)
u.a. 47-54 Donald P. Hansen, Some Early Dynastic I Sealings from Nippur; 69-76 Herbert Hoffmann, An Urartian Decorated Bronze Strip from Diyarbakir; 195-205 Jane C. Waldbaum, A Bronze and Iron Iranian Axe in the Fogg Art Museum.